KASUS PENYAKIT REPRODUKSI PADA KUCING BETINA DI RUMAH SAKIT HEWAN PROFESOR SOEPARWI TAHUN 2013 - , ROMDANI BUDI SAPUTRO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Job Training followed by all students of the Diploma VI semester Veterinary Vocational School. The purpose of this final project to determine the incidence of cases of female reproductive diseases in cats Veterinary Hospital Professor Soeparwi during 2013 and know how to handle that success in sustaining life and cat population that lies in the ability to raise, manage governance rapid reproduction and breeding cats many have children in the birth. Cases are most often found abortion cases representing 10 percent of cases with 42%, followed by endometritis cases amounted to 5 percent of cases with 21%, then distokia 4 cases with a percentage of 17%, prolapse amounted to 2 percent of cases with 8%, fetal maceration totaling 2 the percentage of 8% of cases, fetal mummification amounted to 1 percent of cases with 4%, and retained placenta amounted to 1 percent of cases with 4%. Total cases for the year 2013 amounted to 24 cases of reproduction.